Pediatric Inflammatory Bowel Disease - Mamula, Petar; Grossman, Andrew B.; Baldassano, Robert N.; Kelsen, Judith R.; Markowitz, Jonathan E. (Springer International Publishing : Imprint: Springer, 2017)
The latest edition of this essential text provides a comprehensive overview of the unique pediatric issues of inflammatory bowel disease. Through new and thoroughly revised chapters, the volume features updates regarding pathogenesis, clinic features, and management, with an emphasis on recent understanding of pharmacokinetics and the utilization of cutting edge therapeutic monitoring to maximize efficacy of medical management. The new edition also highlights newer, recently approved drugs, emerging therapies, and the most recent recommendations regarding post-operative management for patients who ultimately require surgery. Written by experts in the field, Pediatric Inflammatory Bowel Disease, Third Edition is a valuable resource for both pediatric and adult gastroenterologists involved in the care of children with inflammatory bowel disease.
Keywords: Medicine.; Gastroenterology.; elektronické knihy; electronic books